The Theory of Nationhood - Heater, Derek. author. aut Link
IX, 196 p.
Keywords: An innovative and entertaining examination of the theory of nationalism. Derek Heater brings together the seven most influential - for good or evil - European thinkers on nationalism from the late eighteenth to the early twentieth century. Herder, Fichte, Mazzini, Mill, Renan, Hitler and Stalin together debate their ideas in a platonic symposium, using the words from their own works in the central part of the book. The first part of the book introduces each thinker in the appropriate historical context, while the third part considers judgements on their thought.